(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
Communicative competence as an important component of the general professional competence of a teacher is directly related to the effectiveness of interaction, communication of a person in accordance with the requirements of pedagogical problem situations that need to be resolved. Communication between people is an extremely complex and delicate process. Inefficiency in communication may be associated with the complete or partial absence of one or another communication skill, for example, the ability to navigate and behave in a particular situation. It can be caused by insufficient self-control, for example, due to the inability to cope with over excitation, impulsiveness, aggression